The Amendments of the Jordanian Penal Code: An Analytical and Critical Perspective - Al-Zoubi , Muath Yahia (Dirasat: Shari’a and Law Sciences, 2020)
This paper deals with the amendments of the Jordanian Penal Code through an analytical and critical perspective. The amendment of the law is an inevitable, essential and urgent need of human nature in every society. This is because people’s lives are constantly changing. Therefore, the Penal Code must be amended whenever necessary as certain acts were previously not a criminal phenomenon, however, now they have become so, and there are acts that were considered a criminal behavior previously. The research adopted the critical analytical approach by determining how the law is applied to related issues, analyzing the texts legally, and stating some of the doctrinal opinions explained in the texts. The comparative approach was also used to compare the texts before and after modification to show the most important differences between the compared texts. The descriptive approach was also used by describing the topics as provided by the law and collecting the information required to find answers to the study questions. The study found that the modified law is based on the legal protection of some groups such as people with disabilities, girls, and women. The modified law also introduced the idea of community-based alternatives to reform. The modified law also criminalized some acts that were not previously criminalized, such as incitement to hatred. The study recommended more research on the subject of the study because some concepts and legal provisions need further study.